A study of topological indices and their bounds with applications to molecular graphs. - Rajpoot, Abhay (IIT(BHU) Varanasi, 2022)
Abstract is available in the attachment.
This Thesis is summited by Abhay Rajpoot who is a Ph.D. Student of IIT(BHU) Varanasi.
Keywords: topological; applications; molecular graphs